Acute Dialysis Quality Initiative (ADQI) XIV Sepsis Phenotypes and Targets for Blood Purification in Sepsis: the BogotÁ Consensus. Issue 3 (March 2016) - Kellum, John A.; Gómez, Hernando; Gómez, Alonso; Murray, Patrick; Ronco, Claudio
Abstract : ABSTRACT: Despite widespread use, there is currently no consensus on how extracorporeal blood purification therapies should be applied or studied in patients with sepsis. One major obstacle has been the lack of clear descriptions of specific sepsis phenotypes tied to mechanisms that would permit the identification of molecular targets. Current evidence suggests that sepsis-related morbidity and mortality involve widely different clinical phenotypes that variably include mitochondrial dysfunction, abnormalities of vascular biology including endothelial dysfunction and coagulopathy, epithelial dysfunction, and immune suppression and dysregulation. While most cases of sepsis involve some element of all of these pathobiologic processes, the magnitude of each varies greatly from patient to patient in part as a result of the pathogen and in part related to host-specific factors. Thus, the purpose of the fourteenth international consensus conference of acute dialysis quality initiative was to develop consensus for a conceptual model of sepsis-induced organ failure that can be treated by extracorporeal blood purification and possibly also with drugs or other therapies. We assembled a group of experts from around the world and used a modified Delphi method to reach consensus. Specific findings and recommendations for future research are provided in the four accompanying papers.